The effect of languaging and teacher corrective feedback on the writing of l2 learners with low proficiency - Sabariah Abd Rahim; Yang Xianjian (Human Resource Management Academic Research Society, 2024)
Low proficiency Second Language (L2) learners often face significant challenges in mastering the skill of writing. Despite having studied the English language for years, they consistently commit grammatical errors and employ incorrect English language and writing practices. To support low proficiency L2 learners in refining their writing skills, teachers offer Corrective Feedback (CF) to address both grammatical and non-grammatical errors. The effectiveness of the CF can also be improved by incorporating languaging into the teacher CF. Thus, the purpose of the present study is to examine the effect of teacher CF and languaging on the writing of low-proficient L2 learners. The study was done on 25 university students with low L2 proficiency, and the data was collected using a qualitative multiple-case research design. To analyse the data, an error ratio and the Wilcoxon signed-rank test were employed. The finding shows that the provision of languaging on the teacher CF facilitated the low proficiency L2 learners’ writing. The study is noteworthy for its application of the mediational tool in the provision and processing of teacher CF and the complementary pedagogical strategy in the pedagogical teaching of writing development for lower proficiency L2 learners.